2015
DOI: 10.1016/j.socscimed.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Education and health knowledge: Evidence from UK compulsory schooling reform

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. For causal identification we use increases in the UK minimum school leaving age in 1947 (from 14 to 15) and 1972 (from 15 to 16) to provide exogenous variation in education. These reforms predominantly induced adolescents who would have left school to stay for one additionally mandated year. OLS estimates suggest that education significantly increases health knowledge, with a one-year increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 27 publications
1
35
2
4
Order By: Relevance
“…The findings stand in stark contrast to the previous literature, which either suggests that education may not have a strong effect on knowledge [3,37], or that knowledge only plays a minor role in the education-health lifestyle relationship [14,41,48].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings stand in stark contrast to the previous literature, which either suggests that education may not have a strong effect on knowledge [3,37], or that knowledge only plays a minor role in the education-health lifestyle relationship [14,41,48].…”
Section: Discussioncontrasting
confidence: 99%
“…They find only weak evidence for education effects on knowledge, concluding that "allocative efficiency is not likely to be the main reason for why education improves health" (p. 811). Similarly, [37], who use data of the UK Health and Lifestyle Survey and compulsory schooling reforms in 1947, do not find education to have a positive effect on knowledge, further challenging the validity of the allocative efficiency argument.…”
Section: Theoretical Framework and Empirical Literaturementioning
confidence: 99%
“…Unlike the papers above which examine the effects of compulsory schooling on health and mortality outcomes, the paper by Johnston et al (2015) investigates the effects on health knowledge. Health knowledge is generally considered to be an important pathway through which education improves health, yet few studies have examined whether education causally influences this knowledge.…”
Section: The Health Benefits Of Compulsory Schooling Are More Apparenmentioning
confidence: 99%
“…The Johnston et al (2015) paper is not the first study to report null effects of education on health-related outcomes when using compulsory schooling laws as an instrument. Indeed, results from studies of the United States and Europe using this approach are quite mixed.…”
Section: The Health Benefits Of Compulsory Schooling Are More Apparenmentioning
confidence: 99%
“…A study by Johnston et al investigated the relationship between education obtained and health knowledge and found that the level of education significantly impacts health understanding. According to their estimates, a one-year increase in schooling can increase health knowledge by 15% (Johnston et al, 2015). As the men in the communities become more educated and the average education level increases, so will the health literacy in the communities.…”
Section: Discussionmentioning
confidence: 99%